Exploring pedagogies for diverse learners online - Rice, Mary Frances, 1980- (Advances in research on teaching ;, 2015)
This proposed volume will profile research projects and methods that are at the top of the innovation curve in terms of their implications for teaching and teacher education. Chapters included in this volume include profiles of cutting edge work on methodological possibilities of studying diversity in online settings, engaging diverse adolescents and their parents in online coursework, working effectively with adolescents in need of credit recovery, pre-empting failure with the practical use of blended coursework for young children, supporting students with various types of disabilities in online settings, problematizing and unpacking the work of teachers in online settings as they plan for and attend to the needs of students who have not succeeded in traditional school situations, examining issues of glocality and ecosophia as pedagogical stances, and framing the work of teacher educators as they conceptualize curriculum to meet the needs of diverse students in taking online courses and thriving in virtual learning environments.